2022
DOI: 10.1038/s41598-022-21912-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and prognosis of acute kidney injury in patients treated with immune checkpoint inhibitors: a retrospective study

Abstract: Immune checkpoint inhibitors (ICIs) change the prognosis of many cancer patients. With the increasing use of ICIs, immune-related adverse events are occurring, including acute kidney injury (AKI). This study aimed to assess the incidence of AKI during ICI treatment and its risk factors and impact on mortality. Patients treated with ICIs at the First Medical Center of the Chinese PLA General Hospital from January 1, 2014, to December 30, 2019, were consecutively enrolled, and risk factors affecting AKI developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…PPIs, which have been associated with the development of AKI in several observational studies [ 12 , 13 , 30 ], were also identified as a key feature in our prediction model. In addition, although not at the top of the list, diuretics, NSAIDs, and baseline renal function features were also identified as key risk factors by the model, as shown in the dependence plot [ 17 ] ( Fig 3c , S4 Fig in S1 File ). Although the dependence plot did not indicate a causal relationship, the prediction model regarded these key features as crucial for predicting AKI.…”
Section: Discussionmentioning
confidence: 99%
“…PPIs, which have been associated with the development of AKI in several observational studies [ 12 , 13 , 30 ], were also identified as a key feature in our prediction model. In addition, although not at the top of the list, diuretics, NSAIDs, and baseline renal function features were also identified as key risk factors by the model, as shown in the dependence plot [ 17 ] ( Fig 3c , S4 Fig in S1 File ). Although the dependence plot did not indicate a causal relationship, the prediction model regarded these key features as crucial for predicting AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common complication in cancer population with an incidence rate that varies from 7.5% to 25% depending on the type of malignancy, criteria used to define AKI, duration of the study, and patients’ comorbidities [15]. Patients receiving ICI therapy have a similar overall AKI incidence, ranging from 5 to 25%, based on real-world data from multiple retrospective studies [611]. Unfortunately, studies that have evaluated the incidence of AKI in patients receiving ICIs have used different criteria to define AKI.…”
Section: Incidence Of Aki In Patients Receiving Ici Therapymentioning
confidence: 99%
“…The acute interstitial nephritis (AIN) is the most common finding in the kidney biopsies of patients with ICI-associated AKI in about 80–90% [14, 15]. However, a spectrum of other glomerulopathies could also be seen, albeit less commonly, including pauci-immune vasculitis, C3 glomerulonephritis, thrombotic microangiopathy, and immune complex glomerulonephritis [612, 16, 17]. Although the median time for diagnosing ICI-associated AKI from the initiation of ICIs to clinical presentation is approximately 3–4 months, it has been reported to occur as early as a few days or as late as 18 months into therapy [14, 15, 18, 19].…”
Section: Incidence Of Aki In Patients Receiving Ici Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Through extensive clinical studies and meta-analyses, several key factors have emerged: Age and sex: Although there are limited data, there appeared to be no notable differences observed with regard to advancing age, male gender, white race, or other pre-existing comorbidities [ 4 , 16 ]. Drugs: Renal irAEs are potentially more prevalent in patients undergoing ICI therapy combined with PPIs, NSAIDs, or antibiotics [ 4 , 17 ]. Combining ICIs with these medications, particularly NSAIDs and PPIs, has been linked to AIN, potentially activating drug-specific T cells, and triggering immune reactions.…”
Section: Diagnosismentioning
confidence: 99%